Rhetorics of blackness, rhetorics of belonging: The politics of representation in black Canadian expressive culture. - Walcott, Rinaldo (Canadian Review of American Studies, 1999)
In this article the author attempts to make a case for a recognition of a politics of black ethnicities. Attention is focused on the rhetorics of pluralism which have conditioned how Canadians imagine who the black Canadian is, and discussed is how it is that these rhetorics have obscured what might be some more important questions. The author states that this essay is an attempt to tentatively discuss not what it might mean to be black in Canada, but rather to conceptualize how the politics of belonging is mapped, charted and articulated by black Canadians. See also: 18264, 18265, 18275, 18304, 18310, 18312, 18316, 18319, 18331, 18338, 18353, 18366, 18384, 18386, 18387, 18397, 18411, 18412, 18413, 18417, 18424, 18428, 18430, 18431, 18432, 18434, 18436, 18440, 18441, 18447, 18454, 18456, 18461, 18463, 18464, 18468, 18470, 18474, 18477, 18478, 18482, 18484, 18485.